Radiation damage in tungsten target of the "KIPT Neutron Source" - Gann, V.V.; Gann, A.V.; Borts, B.V.; Karnaukhov, I.M.; Gladkikh, P.I.; Parkhomenko, A.A. (Вопросы атомной науки и техники, 2021)
In this work, mathematical modeling of a complex of processes occurring in a tungsten target under irradiation with high-energy electrons with an energy of 100 MeV: an electromagnetic shower, the production of photo-neutrons, and particle transport along the target, damage from neutrons of the subcritical assembly. It was found that the greatest contribution to the rate of damage formation in a tungsten target give the elastic scattering of high-energy electrons on nuclei. Проведено математичне моделювання комплексу процесів, що проходять у вольфрамовій мішені при опроміненні високоенергетичними електронами з енергією 100 МеВ: електромагнітного ливню, утворення фотонейтронів, транспорту частинок уздовж мішені, пошкодження від нейтронів підкритичної збірки. Встановлено, що найбільший внесок у швидкість створення пошкоджень у вольфрамовій мішені вносить пружна взаємодія високоенергетичних електронів з ядрами. Проведено математическое моделирование комплекса процессов, проходящих в вольфрамовой мишени при облучении высокоэнергетическими электронами с энергией 100 МэВ: электромагнитного ливня, рождения фотонейтронов, транспорта частиц вдоль мишени, повреждений от нейтронов подкритической сборки. Установлено, что наибольший вклад в скорость образования повреждений в вольфрамовой мишени вносит упругое взаимодействие высокоэнергетических электронов с ядрами.